A chandrashila (moonstone) on the steps of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
The east-facing steps on the adhisthana have a chandrashila (moonstone) on the third step. The chandrashila (moonstone) is a hemispherical stone in the shape of the moon and is often placed at the entrance of Hindu temples and is designed to resemble a lotus flower.